68.6k views
2 votes
3(x – 2) + 4x = 10(x + 1)

( 25 pts 4 answering right)

2 Answers

5 votes

Answer:

x = -5.33333333

Explanation:

Using dist. prop

3x - 6 + 4x = 10x + 10

combine like terms

7x - 6 = 10x + 10

move the 6 over

7x = 10x + 16

move the 10x over

-3x = 16

divide by -3

x = -5.33333333

User Necixy
by
5.2k points
2 votes

Answer:

-16/3

Explanation:

3(x-2) + 4x =10(x+1)

Expand brackets

3x -6 +4x = 10x+10

Collect like terms;

3x+4x -6 =10x+10

7x-6= 10x+10

Collect like terms ;

7x-10x = 10+6

-3x = 166

X = -16/3 = - 5 1/3

User Serbitar
by
5.8k points